Juggling work and home selves: Low identity integration feels less authentic and increases unethicality - Ebrahimi, Mahdi; Kouchaki, Maryam; Patrick, Vanessa M. (Organizational behavior and human decision processes, 2020)
•Low (vs. high) identity integration leads to greater feelings of inauthenticity and unethical behavior.•Inauthenticity mediates the effect of segmentation on unethical behavior.•Support is provided using experimental and field survey data. This research investigates the effect of individuals’ subjective perceptions of the overlap among different identities on their feelings of authenticity and the likelihood of engaging in unethical behavior. Across four studies we found that low (vs. high) identity integration led to greater feelings of inauthenticity and a higher likelihood of engaging in unethical behavior. Manipulation of low (vs. high or control) identity integration led to higher feelings of inauthenticity (Study 1) and greater cheating behavior (Study 2). Feelings of inauthenticity mediated the causal effect of low identity integration on dishonesty (Study 3). In a field survey, using supervisor–employee dyads, we replicated the results from the lab to show that employees who reported lower identity integration felt more inauthentic and were more likely to behave unethically as measured by their supervisors’ report of interpersonal and organizational deviance (Study 4). Our results demonstrate that the manner in which individuals view their multiple identities influences feelings of inauthenticity and unethical behavior.